2019
DOI: 10.1149/ma2019-02/5/445
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Froth-Flotation Separation Process for Direct Recycling of Li-Ion Batteries and Its Technical Feasibility

Abstract: The increasing demand for Li-ion batteries (LIBs) in hybrid and electric vehicles had led to a significant increase in the volume of new and end-of-life LIBs. For this reason, recycling of spent LIBs has attracted significant attention in recent years for future sustainability. Different from existing recycling methods such as pyrometallurgical and hydrometallurgical methods, direct recycling method recovers cathode and anode active materials directly in reusable forms at a low cost. This process consists of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…2017)). 32 It has been suggested that the tension-dependent elastic strain in an R2R process can be modeled using Hooke's Law: 33 T = AEε [3] where A is the cross-sectional area; E is the elastic modulus; and ε is the tensile strain. Thus, for each component, a value of maximum allowable tension can be calculated from the experimental values of E and ε.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2017)). 32 It has been suggested that the tension-dependent elastic strain in an R2R process can be modeled using Hooke's Law: 33 T = AEε [3] where A is the cross-sectional area; E is the elastic modulus; and ε is the tensile strain. Thus, for each component, a value of maximum allowable tension can be calculated from the experimental values of E and ε.…”
Section: Resultsmentioning
confidence: 99%
“…8,9,22 The feasibility of recovering electrode capacity though re-lithiation has already been demonstrated, [23][24][25][26][27][28][29] and preliminary work has suggested that reconditioned electrodes can be analytically indistinguishable from fresh electrodes. 22 To date, all known work with direct recycling has been done at the laboratory scale; 8,[26][27][28][29][30][31][32] as such, comprehensive process engineering optimization has yet to be performed to make this approach viable on an industrial scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation